Inheritance of temperature sensitivity of the photoperiod response in common bean (Phaseolus vulgaris L.) - White, Jeffrey W.; Kornegay, Julia L.; Cajiao V., César Hernando (Springer, 1996)
Photoperiod response of flowering in common bean (Phaseolus vulgaris L.) is thought to be controlled by the genes Ppd and Hr. However, cultivars also vary in the degree that cooler temperatures reduces their sensitivity to photoperiod. To examine the inheritance of this temperature sensitivity, crosses of cvs. Gordo x de Celaya and Flor de Mayo × Rojo 70 were evaluated at two sites differing in mean temperature and using 12.5-h natural photoperiod or 18-h artificially extended photoperiod. Under 18-h photoperiod at the warmer site, Palmira, no plants of the parents or of the F2 populations flowered, confirming that the parents were sensitive to photoperiod. Under 12.5-h photoperiod at the cooler site, Popayan, the parents for each cross flowered at similar dates and no segregation for days to flower was observed. However, under 18-h photoperiod, de Celaya and Rojo 70 and the F1 populations did not flower within 100 days after planting, while the F2 and F3 populations showed segregation that was consistent with single gene inheritance, late flowering being dominant. Late flowering at Popayan under 18-h photoperiod indicates a lack of temperature sensitivity, so temperature insensitivity of the photoperiod response was dominant to sensitivity. The name Tip, for “temperature insensitivity of photoperiod response”, is proposed for this gene, with the recessive form of this gene conditioning earlier flowering at cooler temperatures with long daylengths. It is recognized that the observed segregation patterns could represent the effect of multiple alleles at the Ppd or Hr loci, and studies are proposed to test this possibility with molecular markers and recombinant inbred lines.